Monitoring land cover change and population growth, A study case of Obio/Akpor Local Government Area, Nigeria - M Menegbo, Emmanuel (International Journal of Physical Research, 2022)
Remote Sensing provides earth surface data use in mapping and monitoring the built environment and other land uses. This work aims to monitor land cover change and Population growth in Obio/Akpor LGA, Rivers State, Nigeria using Global Land cover 30 data and Worldpop data between2000 and 2020 for land cover and 2010 to 2020 for population. Global Land cover30 of 2000 - 2020 used to map and detect land cover change while the Worldpop of 2010 and 2020 used to map population growth. The outputs of the work show that artificial surfaces (built-up area)Â increase by 33.75 % from 2000 to 2020, similarly built-up area population will increase by 38.66 % between 2000 and 2020.Bare land recorded the highest expansion of 418.71% from 2000 to 2020. Wetlands reduce by 1.36% and forest also reduces by 37.05%, the effect of deforestation on climate change continues.Â Change detection techniques using Geographic Information System (GIS) and remote sensing remain the most cost effective way of monitoring the environment for better planning and informed decision making.Â Â Â